The species of the genus Empicoris wollf, 1811 (Heteroptera: Reduviidae: Emesinae) newly collected in VietNam - Lam, Truong Xuan (Academia Journal of Biology, 2015)
The present paper describes 3 species of the genus Empicoris Wollf, 1811 (Reduviidae: Emesinae) collected for the first time in Vietnam: Empicoris armatus (Champion, 1898) (fig. 1), Empicoris vagabundus (Linnaeus, 1758)  (fig. 2) and Empicoris sp. (fig. 3). A brief account is given for each species and a synoptic key to there species is appended. The following is the diagnosis of Empicoris sp.. Measurements: ♀, body length: 6-7 mm; maximum of abdomen 4.3 mm. Head length: 0.7 mm; anteocular part: 0.4 mm; length of postocular part: 0.3 mm. Maximum of thorax: 1.6 mm; length of anterior lobe pronotum: 0.35 mm and length of posterior lobe of pronotum: 0.55 mm. Length of hemelytrol: 4.5 mm. Length of antennal joints I:II:III: IV = 7.6:8.2:2.3:1.4; Length of rostral segments I:II:III = 0.5:0.32:0.26. Length of scutellum: 0.06 mm.